Corruption in Construction Industry and Mitigation Actions in the UAE - AL HOSANI, NAWAF MOHAMED (2020)
Corruption and malpractices in Construction Industry become most critical issue in the Construction sector especially in the UAE. Preventive measures are taken to eradicate or minimize the damage and laws are introduce to safeguard the industry. This dissertation is covers the subject and well supported by suggestion by various authors and various literature reviews confirming such situation occurs in the industry across the world. Hence, the construction industry dominated by the multicultural society specially the expatriate community, which they hold the various managerial positions in UAE construction sector, they intent to make quick money through malpractices and get away with the gaps in Contract Clauses and the legal system. After conducting the survey, collecting data and one to one interviews with many industry professionals at many levels, it was well supported as primary and secondary data. After evaluating all data it suggested that many projects from inception to the close out phase, it significantly contribute the corruption and malpractices. |Most of the projects, time is critical and no time go into deep and review the procurement cycle, scope or the construction methodically. It further suggested, eradication of malpractices totally is impossible but preventive measures can be taken to minimize and control the situation in UAE as well as globally. This will help to select the best procurement strategy maintaining the Quality, Time and Cost within the high value and highly complex projects. This is the obligation in all industrial professionals support with the country’s legal frame work to introduce new laws and preventive measures, follow the code of ethics and moral values to support the industry specially the construction sector.